Insights into enzyme mechanisms and functions from experimental and computational methods - Christov, Christo (Senior lecturer in computational biochemistry) (Advances in protein chemistry and structural biology, 2016)
Insights into Enzyme Mechanisms and Functions from Experimental and Computational Methods is the latest volume in the popular Advances in Protein Chemistry and Structural Biology series, an essential resource for protein chemists. Each volume brings forth new information about protocols and analysis of proteins, with each thematically organized volume guest edited by leading experts in a broad range of protein-related topics.